PENERAPAN METODE FORWARD CHAINING DALAM SISTEM PAKAR PENDETEKSI KERUSAKAN AIR CONDITIONER (AC) BERBASIS ANDROID - Aprih Widayanto; Febrian Aji Pratama (Indonesian Journal on Software Engineering (IJSE), 2019)
ABSTRACT The progress of computer technology has helped many people in various fields of life. Expert systems are computer programs with expert knowledge to solve certain problems such as imitating human thought. Air Conditioner (AC) is a machine made to stabilize the humidity of an area and the temperature of the air. The lack of knowledge of the owner of the AC equipment has resulted in the equipment being damaged and the technical maintenance of the AC, and the amount of costs incurred for maintenance services is one of the obstacles. Based on these problems, the author made an expert system application to detect damage to Android-based air conditioners. . This application is expected to help the community in detecting damage, causes and solutions in Air Conditioning (AC). Interview and literature studies are data collection techniques used by the authors. In making the program the author uses the Forward Forward Chaining method. In this application there are 4 main menus, namely diagnosis, info, about and exit. Keywords: Expert System, Air Conditioner (AC), Forward Chaining, Android